II.xvii.4 Election Candidate Portraits, - Labour Party (Ireland) (1990)
Labour Party colour election candidate portraits. Candidates depicted include: Senator Jack Harte (item 66); Sean Ryan TD (item 67); Jim Kemmy TD (item 68); Dick Spring TD (items 68-69); Joe O'FLynn (items 70-71); Tommy Broughan TD (item 74); Lord Mayor John Kelleher, dated Jul 2002 (item 75); Eamon Walsh TD (item 76); Patrick Rabitte TD and Jan O'Sullivan TD (item 77); Senator Ann Gallagher (item 78); Ruairi Quinn TD (items 79-82); Mary Upton TD (item 83); Derek Nolan TD (item 84); and Gerald Nash TD (item 85).